Stylistic diversity in creation of the poetics of a literary work for children (based on T.S. Eliot’s Old Possum’s Book of Practical Cats) - Naumenko, Nataliia (My University, 2016)
The article represents the results of stylistic and literary critical analysis of T.S. Eliot’s poems selected from Old Possum’s Book of Practical Cats (1939). There was shown that the alternation of speech elements had conditioned the special generic palette of the verses, the variety of heir perception by different aged readers, and thus the book could evoke the new wave of interest to animalism in literature.
Keywords: кафедра іноземних мов професійного спрямування; поезія; Еліот; анімалістика; стиль; дитяча література; poetry; animalistics; style; children's literature